Optimizing Instagram in Sociology Materials to Improve Digital Literacy for Junior High School Students - Risnandar, R.; Sakti, Asri Wibawa (Bumi Publikasi Nusantara, 2022)
The development of science and technology currently meets all lines of human life, including the world of education. 21st century learning requires education to always keep up with the times. This study aims to determine students' understanding of social media and how to use it in learning. Then to find out to what extent students use Instagram social media well and wisely. This study uses quantitative methods. Data collection techniques in the form of pre-test and post-test. The results showed that students had knowledge and understanding of Instagram social media. Then students have the ability to operate social media for social studies learning, especially sociology material accompanied by creativity. In addition, students have begun to be wise in using social media. This can be obtained because students are enthusiastic in participating in activities. So that students can understand well. In addition, schools are already implementing online learning.